The Effect of the ReCODE Learning Model on Students' Critical Thinking Skills and Scientific Literacy: - - Ningsih, Endah Suwita; Nopriyeni; Herlina, Meti (PENDIPA Journal of Science Education, 2025)
This study aimed to develop students' critical thinking skills and scientific literacy. This type of research is a quasi-experimental research, using a Non-Randomized Control Group research Design. The sample of this study was divided into 2 groups, namely the experimental group and the control group. The data collection technique was carried out through 5 essay questions for each variable, namely critical thinking skills and scientific literacy skills. The results of the t-test showed that sig. (2-tailed) of 0.000 was smaller than 0.05, which means there was an influence on the critical thinking skills and scientific literacy of MTsN 2 Kaur students. Teachers are advised to start implementing the ReCODE model gradually, especially in science learning that emphasizes conceptual understanding and high-level thinking. Schools and policy makers are expected to provide support in the form of adequate training and learning facilities.